The effect of supportive educative intervention based on the theory of planned behavior on self-care in patients with type 2 Diabetes - Martawinarti, RTS Netisa; Ekawaty, Fadliyana; Sari, Yulia Indah Permata; Mulyani, Sri; Oktaria, Rina (Riset Informasi Kesehatan, 2024)
Background: Self-care for adults with diabetes is complex because they live with a chronic condition that requires long-term management of medication, dietary regulation, and other factors that affect their blood sugar levels. This necessitates special attention based on the individual’s medical condition and environment. Method: This study uses a quasi-experimental design with a pre-post test design. The sample size in this study consists of 33 participants in the intervention group and 33 participants in the control group. The instruments used are the Diabetes Self-Management Instrument (DSMI) and the Theory of Planned Behavior (TPB) questionnaire Results: The results of this study indicate an effect on the intervention group regarding self-care in patients with type 2 diabetes mellitus, as evidenced by a p-value of 0.000, which means there is an influence from the intervention group compared to the control group. Conclusion: The intention of individuals with diabetes to engage in self-care is influenced by attitudes, subjective norms, and behavioral control obtained from their environment, support systems, and experiences. Accurate information, support from close relatives, and learning from experiences shape the mindset of patients, encouraging them to adopt a positive attitude.